2012
DOI: 10.4236/ojas.2012.24039
|View full text |Cite
|
Sign up to set email alerts
|

Bovine trypanosomosis: A threat to cattle production in Chena district, southwest Ethiopia

Abstract: A cross-sectional study to determine the prevalence of bovine trypanosomosis was carried out in Chena district, Kefa zone, southwest Ethiopia from September 2010 to January 2011. Blood samples were collected from 391 randomly selected local (zebu) breed cattle in three representative peasant associations (PAs). The buffy coat and Giemsa stained thin blood films examination techniques were used for parasite detection and identification. The packed cell volume (PCV) estimation was also conducted. From a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
4
6
1
Order By: Relevance
“…This result is consistent with the work of Teka et al [5] which reported 4.43% bovine trypanosomosis prevalence in selected villages of Arba Minch; Adale and Yassine [7] which reported 6.3% in Wolaita zone of Kindo Koish district, Southern Ehiopia; Degneh et al [8] reported 6.86% in Lalo Kile district of Oromia regional state; Alamayew et al [9] which reported 6.9% in Chena district, south west Ethiopia and Denbarga et al [10] which reported 4.2% in South Achefer district, Northern Ethiopia.…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with the work of Teka et al [5] which reported 4.43% bovine trypanosomosis prevalence in selected villages of Arba Minch; Adale and Yassine [7] which reported 6.3% in Wolaita zone of Kindo Koish district, Southern Ehiopia; Degneh et al [8] reported 6.86% in Lalo Kile district of Oromia regional state; Alamayew et al [9] which reported 6.9% in Chena district, south west Ethiopia and Denbarga et al [10] which reported 4.2% in South Achefer district, Northern Ethiopia.…”
Section: Discussionsupporting
confidence: 82%
“…The overall prevalence of bovine trypanosomosis was 21.25% which was higher when compared with previous reports in different parts of the country, such as 1.3% in Arbaminch by Girma et al 16 6.9% in Chena district by Alemayehu et al 17 altitude, rainfall, and temperature and livestock management system. But the research was agreed with NTTICC 20 with prevalence of 22% in Gari settlement area.…”
Section: Entomological Findingscontrasting
confidence: 55%
“…Similar results have been found in several previous studies [ 6 , 26 29 ]. This could be attributed to differences in the period of exposure to vectors between the cattle age groups [ 28 ]. In traditional grazing systems, suckling calves are restricted or grazed at homesteads and not allowed to graze with adults until weaned off [ 27 ].…”
Section: Discussionmentioning
confidence: 99%